HMGA2 promotes cancer metastasis by regulating epithelial–mesenchymal transition - Ma, Qing; Ye, Sisi; Liu, Hong; Zhao, Yu; Mao, Yan; Zhang, Wei (Frontiers in Oncology, 2024)
Epithelial-mesenchymal transition (EMT) is a complex physiological process that transforms polarized epithelial cells into moving mesenchymal cells. Dysfunction of EMT promotes the invasion and metastasis of cancer. The architectural transcription factor high mobility group AT-hook 2 (HMGA2) is highly overexpressed in various types of cancer (e.g., colorectal cancer, liver cancer, breast cancer, uterine leiomyomas, etc.) and significantly correlated with poor survival rates. Evidence indicated that HMGA2 overexpression markedly decreased the expression of epithelial marker E-cadherin (CDH1) and increased that of vimentin (VIM), Snail, N-cadherin (CDH2), and zinc finger E-box binding homeobox 1 (ZEB1) by targeting the transforming growth factor beta/SMAD (TGFβ/SMAD), mitogen-activated protein kinase (MAPK), WNT/beta-catenin (WNT/βcatenin) signaling pathways. Furthermore, a new class of noncoding RNAs (miRNAs, circular RNAs, and long noncoding RNAs) play an essential role in the process of HMGA2-induced metastasis and invasion of cancer by accelerating the EMT process. In this review, we discuss alterations in the expression of HMGA2 in various types of cancer. Furthermore, we highlight the role of HMGA2 induced-EMT in promoting tumor growth, migration, and invasion. More importantly, we discuss extensively the mechanism through which HMGA2 regulates the EMT process and invasion in most cancers, including signaling pathways and the interacting RNA signaling axis. Thus, the elucidation of molecular mechanisms that underly the effects of HMGA2 on cancer invasion and patient survival by mediating EMT may offer new therapeutic methods for preventing cancer progression.